WRITING PRACTICE THROUGH PARALLEL WRITING TECHNIQUE TO IMPROVE STUDENTSâ WRITING SKILLS - Shanty, Halim (Institut Agama Islam Negeri Palopo, 2014)
This paper describes and offers writing practice through parallel writing technique to improve studentsâ writing skill. This technique show, how to express their ability with use their own words in written text. The concept of parallel writing technique is central to teaching of connected discourse since it the students should have a model from which work guide them towards their own ability to express themselves in written English. Parallel writing is one of technique that can improve our own idea, main, and opinion in writing. Parallel writing is written version immediately stage. When the students might see a short piece of connected writing by using the new language and then be asked to write a similar piece with use their own word.